Time and difference in rabbinic Judaism - Kattan Gribetz, Sarit (Princeton University Press, 2020)
How the rabbis of late antiquity used time to define the boundaries of Jewish identity. The rabbinic corpus begins with a question-"when?"-and is brimming with discussions about time and the relationship between people, God, and the hour. Time and Difference in Rabbinic Judaism explores the rhythms of time that animated the rabbinic world of late antiquity, revealing how rabbis conceptualized time as a way of constructing difference between themselves and imperial Rome, Jews and Christians, men and women, and human and divine.In each chapter, Sarit Kattan Gribetz explores a unique aspect of rabbinic discourse on time. She shows how the ancient rabbinic texts artfully subvert Roman imperialism by offering "rabbinic time" as an alternative to "Roman time." She examines rabbinic discourse about the Sabbath, demonstrating how the weekly day of rest marked "Jewish time" from "Christian time." Gribetz looks at gendered daily rituals, showing how rabbis created "men's time" and "women's time" by mandating certain rituals for men and others for women. She delves into rabbinic writings that reflect on how God spends time and how God's use of time relates to human beings, merging "divine time" with "human time." Finally, she traces the legacies of rabbinic constructions of time in the medieval and modern periods.Time and Difference in Rabbinic Judaism sheds new light on the central role that time played in the construction of Jewish identity, subjectivity, and theology during this transformative period in the history of Judaism